Integrative microRNAome analysis of skeletal muscle of Colossoma macropomum (tambaqui), Piaractus mesopotamicus (pacu), and the hybrid tambacu, based on next-generation sequencing data - Fantinatti, Bruno E. A. [UNESP]; Perez, Erika S. [UNESP]; Zanella, Bruna T. T. [UNESP]; Valente, Jéssica S. [UNESP]; de Paula, Tassiana G. [UNESP]; Mareco, Edson A.; Carvalho, Robson F. [UNESP]; Piazza, Silvano; Denti, Michela A.; Dal-Pai-Silva, Maeli [UNESP] (Springer Nature, 2021)
Background: Colossoma macropomum (tambaqui) and Piaractus mesopotamicus (pacu) are good fish species for aquaculture. The tambacu, individuals originating from the induced hybridization of the female tambaqui with the male pacu, present rapid growth and robustness, characteristics which have made the tambacu a good choice for Brazilian fish farms. Here, we used small RNA sequencing to examine global miRNA expression in the genotypes pacu (PC), tambaqui (TQ), and hybrid tambacu (TC), (Juveniles, n = 5 per genotype), to better understand the relationship between tambacu and its parental species, and also to clarify the mechanisms involved in tambacu muscle growth and maintenance based on miRNAs expression. Results: Regarding differentially expressed (DE) miRNAs between the three genotypes, we observed 8 upregulated and 7 downregulated miRNAs considering TC vs. PC; 14 miRNAs were upregulated and 10 were downregulated considering TC vs. TQ, and 15 miRNAs upregulated and 9 were downregulated considering PC vs. TQ. The majority of the miRNAs showed specific regulation for each genotype pair, and no miRNA were shared between the 3 genotype pairs, in both up- and down-regulated miRNAs. Considering only the miRNAs with validated target genes, we observed the miRNAs miR-144-3p, miR-138-5p, miR-206-3p, and miR-499-5p. GO enrichment analysis showed that the main target genes for these miRNAs were grouped in pathways related to oxygen homeostasis, blood vessel modulation, and oxidative metabolism. Conclusions: Our global miRNA analysis provided interesting DE miRNAs in the skeletal muscle of pacu, tambaqui, and the hybrid tambacu. In addition, in the hybrid tambacu, we identified some miRNAs controlling important molecular muscle markers that could be relevant for the farming maximization.
Keywords: Fish; miRNAoma; Skeletal muscle